The Impact of the 1918 Influenza Pandemic on the Demography of the Island of Newfoundland in the First Half of the Twentieth Century - Sattenspiel, Lisa; van Doren, Taylor P.; Dimka, Jessica (Newfoundland and Labrador Studies)

(untitled) (Faculty of Arts, Memorial University, 2023)
The early twentieth century was a time of dramatic social, economic, political, demographic, and health-related change in Newfoundland and Labrador. One of the major upheavals at this time was the 1918 influenza pandemic, which led to the deaths of nearly 2,000 residents of the Dominion. In this paper we examine the short- and long-term demographic consequences of this catastrophic event. We focus on changes in the overall age and sex distribution, fertility levels, and cause-specific (for selected causes) and overall mortality before, during,and after the 1918 pandemic. Data on these demographic processes and the prevalent social conditions have been collected at The Rooms, the Digital Archives at Memorial University of Newfoundland, and other archives in the province and online. Results indicate that, although the 1918 pandemic had major impacts over the short term on fertility, mortality, and the age and sex structure, both on the island as a whole and in every region analyzed, these effects were of short duration. Long-term demographic changes occurring on the island duringthe first half of the twentieth century appear to be more related to the large-scale socio-economic changes that occurred through the long process of moving from an independent Dominion to Confederation with Canada.